2017
DOI: 10.12669/pjms.331.11617
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of transconjunctival sutureless 27-gauge micro‑incision vitrectomy surgery in diabetic vitreous haemorrhage

Abstract: Objective:To evaluate the visual outcomes of 27-gauge transconjunctival sutureless vitrectomy surgery and its complications in patients with diabetic vitreous hemorrhage.Methods:A quasi-experimental study was conducted where eighty seven eyes of 87 uncontrolled type II diabetes mellitus patients presenting with diabetic vitreous hemorrhage were selected to undergo 27-gauge transconjunctival sutureless micro-incision vitrectomy surgery. Main outcome measured was best corrected visual acuity (BCVA). Post-operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…also showed that 27G vitrectomy was useful in diabetic vitreous hemorrhage. [ 10 ] However, these studies did not evaluate the cases on the basis of anatomical status of retina and did not mention how many of their cases had TRD, secondary RRD, thick FVP, and VPT. We retrospectively evaluated complex diabetic vitrectomy cases only and were able to tackle all these complex situations in a satisfactory way.…”
Section: Discussionmentioning
confidence: 99%
“…also showed that 27G vitrectomy was useful in diabetic vitreous hemorrhage. [ 10 ] However, these studies did not evaluate the cases on the basis of anatomical status of retina and did not mention how many of their cases had TRD, secondary RRD, thick FVP, and VPT. We retrospectively evaluated complex diabetic vitrectomy cases only and were able to tackle all these complex situations in a satisfactory way.…”
Section: Discussionmentioning
confidence: 99%
“…However, the vitrectomy efficiency improved dramatically by changing the drive system of the vitrectomy machine 3,4 and by developing a bi-blade vitreous cutter 5,6 . Although the debate on shaft stiffness is still ongoing, an increasing number of reports have found that these instruments pose no problem in surgical procedures [7][8][9][10][11] . There were concerns about inadequate light intensity with the light pipe, although the light source was changed from halogen to xenon and/or mercury vapor and chandelier lighting has also become commonplace 12,13 , thereby securing sufficient light intensity.…”
Section: Impact Of Different Manufacturers and Gauge Sizes On The Permentioning
confidence: 99%
“…There are virtually no problems now regarding brightness of the surgical field during surgery. Thus, many recent reports have found that 27G vitrectomy is sufficiently practical and useful in the treatment of various vitreoretinal diseases, which was initially regarded as difficult [7][8][9][10][11] .…”
Section: Impact Of Different Manufacturers and Gauge Sizes On The Permentioning
confidence: 99%
“…In 2010, Oshima et al ( 7 ) first reported 100% anatomic success and 65% visual improvement of ≥3 lines using a novel 27-gauge (27-G) PPV system in patients with vitreoretinal diseases. Small-gauge vitrectomy has become popular due to its notable advantages, including less trauma, shortened convalescence, reduced inflammatory response and improved manoeuvrability ( 8 ). As a result, the use of 27-G PPV has expanded from simple macular diseases to complicated cases, including rhegmatogenous retinal detachment (RRD) ( 9 ).…”
Section: Introductionmentioning
confidence: 99%